Influence of coarse coal gangue aggregates on properties of structural concrete with nano silica. (2023) - Al Khazaleh, Mahmoud; Kumar, P. Krishna; Mohamed, M. Jinnah Sheik; Kandasamy, A.
Abstract: This paper presents the properties of structural concrete influenced by replacing, coarse aggregate with Coarse coal gangue and cement with nano-silica. Coarse coal gangue is an important solid waste in the mining industry. In India, the annual deposition of coal gangue is about 50 to 60 tons. Large numbers of research work are being carried out intensely to find a feasible way to reuse the coarse coal gangue in concrete thereby reducing the environmental hazard. This paper reports the workability, compressive strength, flexural strength, split tensile strength, shrinkage, sorptivity, and thermal conductivity of structural concrete. Coal gangue as replacement of coarse aggregate and nano-silica as partial replacement of cement was used in this study. The natural Coarse Aggregate (CA) was replaced by Coarse Coal Gangue Aggregate (CCGA) at 0 %, 25 %, 50 %, 75 % and 100 % by weight of coarse aggregate and cement was replaced by Nano-Silica (NS) at 0 %, 2 %, and 3 % by weight of cement. The water to binder ratio was maintained as 0.45. In order to avoid workability reduction during replacement of nano-silica, Naphthalene-based superplasticizer Sulfonated Naphthalene Formaldehyde (SNF) was used to maintain the workability of concrete. The objective of the study is to establish the optimal content of NS and CCGA in the structural concrete with better strength and performance. The test results were compared with conventional M30 grade concrete. Totally 15 different mixes were studied and their test results were interpreted in this paper. The study revealed that cement replacement by 2 % NS by its weight and NA replacement by CCGA at 25 % by its weight showed improved mechanical properties like compressive strength, split tensile strength, and flexural strength. Hence the optimum use of NS and CCGA not improves the strength of concrete but also address the potential way of disposing CCGA.